Understanding the contribution of stretch-activated ion channels to cardiac arrhythmogenesis using computational modelling. (19th May 2022) - Buonocunto, M; Lyon, A; Delhaas, T; Heijman, J; Lumens, J
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Dutch heart foundation, ERA-CVD Introduction: Cardiac electrophysiology and mechanics are strongly interconnected. Among other things, their interaction is mediated by cardiac mechano-electric feedback through stretch-activated ion-channels (SACs). These channels are also thought to contribute to the development of arrhythmias, but their precise role remains unclear. Purpose: To elucidate the contribution of SACs to arrhythmias using a novel computational model of cardiac electromechanics. Methods: We implemented two types of SACs in the O'Hara-Rudy model (ORd) of human ventricular electrophysiology: potassium-selective SACs and non-selective SACs (conducting sodium and potassium). The model was calibrated based on experimental human and rodent data of cardiomyocytes undergoing stretch. The calibration also considered inter-species differences, age, and upregulation of SACs under disease conditions. Subsequently, we varied the amplitude, duration, and timing of the simulated stretch to investigate their effects on action potential (AP). Results: The model reproduced APs measured experimentally. Early afterdepolarizations, delayed afterdepolarizations, and ectopic beats were observed when applying stretch with short duration (e.g. 20ms) and high amplitude (e.g. 40%). When varying the time of application, stretch applied closer to the subsequent beat (cycle length: 1000ms) also shortened the following AP duration (APD) (shortening of 30ms with stretch at t=600ms, 130ms at t=800ms). Higher sensitivity to stretch was observed when simulating disease-related remodelling of SACs. Milder effects (no APD shortening with stretch at t=600ms and t=800ms) were seen with a lower stretch amplitude (e.g. 10% with SACs disease-related remodelling, 15% without). Failure of repolarization only occurred when sustained stretch (1000ms duration) of more than 10% (with SACs disease-related remodelling) or 15% (without) was applied. Conclusions: Using a novel human electromechanical computational model, we quantified the contribution of SACs to cardiac AP changes. We showed that both disease-related SAC remodelling and variations of amplitude, timing, and duration of cardiomyocyte stretch modulated the effects on cardiac electrophysiology. We also showed that SACs may lead to afterdepolarizations and shorten the subsequent AP duration, factors which may potentially contribute to the generation of arrhythmias.